Reliability of the Bond Graph Approach for Robust Diagnosis of a Newborn Incubator System (London Journal of Engineering Research, 2024)
This article aims to solve a problem of research with a thermal system (incubator) to the graph of pseudo-connections. The method we develop is based on the determination of the resolution on the model ARR-BGM (Analytical Redundant Relationships Bond Graph). These relationships serve to detect and isolate faults in the various elements of the system, but also to locate the industrial system. We introduced defects in the heat source, leaks in the incubators and a leak in the incubator door; these defects were transferred by thermal transfer to negative values. The results of simulation, the effectiveness of proposed method to detect and locate defects, in addition, to analyze the robustness of the Incubator to defects, we imported the graphical link model as linear fractional transformations (BG-LFT). This makes it possible to verify the reliability of the approach of the link graphs in terms of sensitivity and detectability of defects that may appear in an industrial system.
Keywords: TELEMAC; SISYPHE; bed roughness; Shield coefficient; bed load transport formulae; Gain Size; hydromorphological modeling; sediment transport; numerical simulation; river engineering.; Incubator; robust diagnosis; bond graph approach; linear fractional transformations; analytical redundancy relations